2017
DOI: 10.3233/jad-161016
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Future Cognitive Performance and Cognitive Decline in Elderly Patients with Cardiovascular Disease

Abstract: IR is related to subsequent poorer cognitive performance and greater cognitive decline among patients with cardiovascular disease with and without diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 35 publications
1
25
0
3
Order By: Relevance
“…Evidence has gathered suggesting that BIR seems to be a shared pathological feature of metabolic and cognitive disturbances in T2DM, obesity, cardiovascular disease, and dementia patients (Kullmann et al 2016;Lutski et al 2017), which may provide the missing link between these disorders. Indeed, recent evidence suggests that insulin resistance is related to subsequent poorer cognitive performance and greater cognitive decline among patients with cardiovascular disease with and without diabetes (Lutski et al 2017).…”
Section: Glycemic Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has gathered suggesting that BIR seems to be a shared pathological feature of metabolic and cognitive disturbances in T2DM, obesity, cardiovascular disease, and dementia patients (Kullmann et al 2016;Lutski et al 2017), which may provide the missing link between these disorders. Indeed, recent evidence suggests that insulin resistance is related to subsequent poorer cognitive performance and greater cognitive decline among patients with cardiovascular disease with and without diabetes (Lutski et al 2017).…”
Section: Glycemic Controlmentioning
confidence: 99%
“…Indeed, recent evidence suggests that insulin resistance is related to subsequent poorer cognitive performance and greater cognitive decline among patients with cardiovascular disease with and without diabetes (Lutski et al 2017). Clinical investigation of the link between the obesity and BIR showed that obese men respond to cognitive but not to catabolic brain insulin signalling (Hallschmid et al 2008), indicating that not all insulin activities in the brain have been equally affected by BIR and that insulin resistance in metabolic disorders does not uniformly affect all target cells and intracellular signaling pathways in the brain (Könner and Brüning 2012).…”
Section: Glycemic Controlmentioning
confidence: 99%
“…Additionally, characteristics related to type 2 diabetes, including higher blood glucose levels, higher serum fasting insulin and insulin resistance [12][13][14], have been linked to cognitive dysfunction, accelerated cognitive decline and dementia in elderly individuals, even in those without diabetes [14,15]. Moreover, in addition to blood glucose and HbA 1c levels, poor long-term HbA 1c trajectories [16] and glucose peaks [17] have been shown to be associated with cognitive function.…”
Section: Type 2 Diabetes Precedes Cognitive Dysfunctionmentioning
confidence: 99%
“…Сравнительно меньше изучено поражение головного мозга при СД -диабетическая энцефалопатия (ДЭ). При ДЭ поражение головного мозга рассматривается с точки зрения нарушения чувствительности клеток головного мозга к инсулину -инсулинорезистентности (ИР), что сближает патогенез ДЭ с патогенезом болезни Альцгеймера (БА) [3]. ИР определяется как патологическое состояние, при котором клетки утрачивают способность ответа на метаболическую активность инсулина и инсулинопосредованных процессов в головном мозге, включая пищевое поведение, продукцию глюкозы печенью, мобилизацию жировой массы, терморегуляцию, ответ на гипогликемию и нейрональные функции, что может являться индикатором ИР [4].…”
Section: обзорыunclassified